Performance of site-specific nutrient management for irrigated, transplanted rice in Northwest India - Khurana, Harmandeep S.; Phillips, Steven B.; Bijay-Singh; Dobermann, Achim; Sidhu, Ajmer S.; Yadvinder-Singh; Peng, Shaobing (Wiley, 2007)
Like in other parts of Asia, irrigated, transplanted rice (Oryza sativa L.) yield increases in Punjab, India, have slowed down in recent years. Further yield increases are likely to occur in smaller increments through fine‐tuning of crop management mainly by accounting for the large spatial and temporal variation in soil characteristics. On‐farm experiments were conducted from 2002 to 2004 at 56 sites in six key irrigated rice‐wheat (Triticum aestivum L.) domains of Punjab to evaluate an approach for site‐specific nutrient management (SSNM). Field‐specific N–P–K applications were calculated by accounting for the indigenous nutrient supply, yield targets, and nutrient demand as a function of the interactions between N, P, and K. The performance of SSNM was tested for two rice crops. Compared with the current farmers' fertilizer practice (FFP), average grain yield increased from 5.1 to 6.0 Mg ha−1, while plant N, P, and K accumulations increased by 13 to 15%. The gross return above fertilizer cost (GRF) was about 14% greater with SSNM than with FFP. Improved timing and/or splitting of fertilizer N increased N recovery efficiency from 0.20 kg kg−1 in FFP plots to 0.30 kg kg−1 in SSNM plots. The agronomic N use efficiency was 83% greater with SSNM than with FFP. The year‐wise effect on all parameters was, however, nonsignificant. As defined in our study, SSNM has potential for improving yields and nutrient efficiency in irrigated, transplanted rice.